Development of Interactive Multimedia Based Learning Media on Set Materials - Dinar Riaddin; Artika Umasugi (Indo-MathEdu Intellectuals Journal, 2021)
This research aims to find out the development of interactive multimedia-based learning media in the material of class VII MTs Negeri Ambon. This research uses Research and Development with development models proposed by Thiagarajan, Semmel, and Semmel. The development research stage consists of 4 stages known as 4D models, namely define, design, develop, and disseminate. The results of this study showed that interactive multimedia-based learning media was declared very valid, judging from the final results of the assessment of media validators and materials by 89 percent with criteria that are very valid or worth using without revision. Interactive multimedia-based learning media is stated to be very practical with the dissemination of student response questionnaires, meeting positive categories. Obtaining scores of 86.43 percent with very practical criteria and worthy of use without revision, interactive multimedia-based learning media is otherwise quite effectively used in known learning from student N-Gain results of 0.66 or 66 percent with moderate categories. Interactive multimedia-based learning media developed meets the valid, effective, and practical categories. It deserves to be used in mathematics learning on set material for students of class VII MTs. Negeri Ambon.